Analisis sektor ekonomi provinsi kalimantan timur - Mahrita Mahrita; Sri Mintarti; Fitriadi Fitriadi (INOVASI, 2016)
An area is said to have featured sector if the economic sectors included in the group's economic base, the growth rate is fast and strong competitiveness.The purpose of this study was to determine the economic sector including the group's economic base, economic sector rapid growth rate and economic sectors that have strong competitiveness. his study uses secondary data obtained at the Central Statistics Agency (BPS) National. This study took the data for the period 2003-2013. The results of this study using the analysis location quotien (LQ) and Analysis Shift Share and quadrant analysis which shows that the economic sector is categorized sector basis in was mining and quarrying and manufacturing, sectors that have a rapid growth rate in the economic shift is sector electricity, gas and water utilities, construction, trade, hotels and restaurants, transport and communications sector, the financial sector and the service sector - services. The sector that has strong competitiveness are agriculture, mining and quarrying, electricity, gas and water supply, construction, trade, hotels and restaurants and financial sector and the service sector - services. Sectors that its growth rate is relatively progressive (forward) is the sector of electricity, gas and water utilities, construction, trade, hotels and restaurants, transport and communications sector, the financial sector and the service sector - services.Keyword: Economic Sectors, Analysis of Location Quotient (LQ), shift share Analysis